Correlation between Anatomopathological Aspects and Pelvic Pain in Women with Deep Infiltrating Endometriosis - Yela, Daniela Angerame; Silva, Mariana Sousa Sguerra; Eloy, Larissa; Benetti-Pinto, Cristina Laguna (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2023)
Objective To correlate the morphological aspects with pelvic pain in women with deep infiltrating endometriosis.Methods A retrospective study with 67 women with deep endometriosis who underwent surgical treatment in a tertiary hospital from 2007 to 2017. The following variables were considered: age, parity, body mass index, site of involvement, hormonal treatment before surgery, pelvic pain, and morphometric analysis. The histological slides of the surgical specimens were revised and, using the ImageJ software for morphometric study, the percentages of stromal/glandular tissues were calculated in the histological sections.Results The mean age of the women was 38.9 ± 6.5 years. The mean pain score was 8.8 ± 1.9 and the mean time of symptomatology was 4.7 ± 3.5 years, with 87% of the patients undergoing hormone treatment prior to surgery. The average expression of CD10, CK7, and S100 markers was 19.5 ± 11.8%, 9.4 ± 5.9%, and 7.9 ± 5.8% respectively. It was found that the greater the expression of CD10, the greater the level of pain (p = 0.02). No correlation was observed between the expression of CD10, CK7, and S100 markers and age and duration of symptoms.Conclusion Women with deep infiltrating endometriosis have a positive association between the level of pain and the fibrosis component in the endometrial tissue's histological composition.
Keywords: Deep infiltrating endometriosis; Histology; Pain